1999
DOI: 10.1161/01.atv.19.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Pharmacological Regulation of Apolipoprotein C-II Gene Expression

Abstract: Abstract-Increased plasma triglyceride concentrations are often observed in metabolic disorders predisposing to coronary heart disease. Among the major determinants of plasma triglyceride metabolism are the apolipoproteins (apos) of the C class, C-I, C-II, and C-III. Whereas physiological concentrations of apo C-II are required for lipolysis of triglycerides by lipoprotein lipase (LPL), overexpression of all 3 C apolipoproteins leads to hypertriglyceridemia. In the present study, we investigated apo C-II gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 54 publications
2
14
1
Order By: Relevance
“…Apo-CII has an important role as activator of lipoprotein lipase, and patients with Apo-CII deficiency are afflicted with severe hypertriglyceridemia (Breckenridge et al 1978). In contrast to the observed upregulation of Apo-CII in the present study, this gene has previously been reported to be slightly downregulated by fenofibrate in primary human hepatocytes (Andersson et al 1999), which indicates a more complex regulatory mechanism of this gene in vivo. Cyp4A-10 (microsomal -hydroxylation), which is a known PPAR-target (Bell et al 1993), was the most highly drug-induced clone identified, and this gene is, like PPAR-itself, downregulated by the high-fat diet (Fig.…”
Section: Discussioncontrasting
confidence: 94%
“…Apo-CII has an important role as activator of lipoprotein lipase, and patients with Apo-CII deficiency are afflicted with severe hypertriglyceridemia (Breckenridge et al 1978). In contrast to the observed upregulation of Apo-CII in the present study, this gene has previously been reported to be slightly downregulated by fenofibrate in primary human hepatocytes (Andersson et al 1999), which indicates a more complex regulatory mechanism of this gene in vivo. Cyp4A-10 (microsomal -hydroxylation), which is a known PPAR-target (Bell et al 1993), was the most highly drug-induced clone identified, and this gene is, like PPAR-itself, downregulated by the high-fat diet (Fig.…”
Section: Discussioncontrasting
confidence: 94%
“…Pharmacological investigations have indicated that the ability of fenofibrate to reduce hepatic and serum lipid levels may be related to several biochemical actions. In essence, fenofibrate was found to stimulate the lipolysis and the elimination of triglyceride-rich particles from plasma by activating lipoprotein lipase and reducing the production of apolipoprotein C-III, an inhibitor of lipoprotein lipase activity, as well as inducing enzymes for catalyzing β-oxidation of fatty acids in mitochondria (Andersson et al 1999;Miura et al 2005). Unlike fenofibrate which could decrease serum total cholesterol level, schisandrin B did not produce any effect in this regard.…”
Section: Discussionmentioning
confidence: 96%
“…ApoC-III inhibits the hydrolysis of triacylglycerols by LPL [80] and the apoE mediated clearance of chylomicron remnants by hepatocytes. The suppression of human apoC-III in transgenic mice by the PPARα activator nafenopin led to the suggestion that the decreased inhibition of LPL increased triacylglycerol clearance from blood [80,81]. The mechanism of this negative regulation, however, has not been resolved yet.…”
Section: Fatty Acid Clearance From Bloodmentioning
confidence: 99%